The Monitoring of Evaluation Soft Skill Students Based on Android with Dynamic Programming Algorithm - Ali, Mahrus (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.117, 2017)
According to search results and studies (IllahSailah, 2008) there is a difference in need and development as well as a perspective on hard skills and soft skills, Between the world of work / business and college at this time the ratio of the needs of soft skills and hard skills in the world of work / business inversely proportional to its development in college. Success in the world of work / effort 80% is determined by soft skills) it has and 20% is determined by hard skills. In Wikipedia (2010) it is written that soft skills is a sociological termination for a person's Emotional Intelligence Quotient (EQ), is the ability of how people relate to one another, such as communicating, listening, giving feedback, working together in a team , Solve problems, contribute to meetings, and resolve conflicts. However, the condition of university students hasyimasy'ari is not aware of the importance of softskill ability. Therefore, researchers make an application for measuring or self-assessing students related sofskill based android premises dynamic programming algorithm. Because android applications are now mushrooming among young people, especially students. This application can display the score of the value amount of softskill.